Populasi Bakteri Pelarut Fosfat, P-Potensial Dan Hasil Jagung Yang Dipengaruhi Oleh Aplikasi MPF Pada Ultisols Jatinangor - Betty Natalie Fitriatin; Mayang Agustina; Reginawanti Hindersah (Faculty of Agriculture, Pattimura University, 2017)
Ultisol is low fertility soil and as low available P due to P fixation by Al and Fe. The phosphate solubilizing microbes (PSM) is the microbial group that enable realease fixed-P to soil solution and be absorbed by plant. This research was aimed to determine the effects of PSM biofertilizer and phosphate fertilizer dosage combination on soil potential P, total phosphate solubilizing bacteria (PSB) population and yield of maize (Zea mays L.) grown in Ultisols. This research used a Randomized Block Design that consist of nine treatments with three replications. The treatments were 100 kg ha-1 of SP-36 fertilizer, 50 kg ha-1 of PSM biofertilizer, SP-36 fertilizer (50 kg ha-1 and 100 kg ha-1) with PSM biofertilizer (25 kg ha-1, 50 kg ha-1 and 75 kg ha-1) repectively. The result showed that the combination of PSM and phosphate fertilizer dosage had significantly effect on PSB total population and maize yield, but did not not on potential P. This experiment suggested that SP-36 fertilizer with 50 kg ha-1 dosage and PSM biofertilizer with 50 kg ha-1 dosage is the best combination.